Oxytocin Receptor Signaling in Vascular Function and Stroke - McKay, Erin C.; Counts, Scott E. (Frontiers in Neuroscience, 2020)
The oxytocin receptor (OXTR) is a G protein-coupled receptor with a diverse repertoire of intracellular signaling pathways, which are activated in response to binding oxytocin (OXT) and a similar nonapeptide, vasopressin. This review summarizes the cell and molecular biology of the OXTR and its downstream signaling cascades, particularly focusing on the mnemonic, stress, and vasoactive functions of OXTR signaling in humans and animal models, as well as the clinical applications of OXTR targeting CNS disorders such as cerebrovascular accidents.